2000
DOI: 10.1063/1.481628
|View full text |Cite
|
Sign up to set email alerts
|

1,2-propanediol and 1,3-propanediol homogeneous nucleation rates and phase transitions in the new phase critical embryos

Abstract: Nucleation rates of supersaturated vapors near the conditions for the critical line for each pair of 1,2- or 1,3-propanediol and carbon dioxide or sulfur hexafluoride at total system pressures of P=0.10, 0.20, and 0.30 MPa have been measured in a flow diffusion chamber. Critical parameters, i.e., temperatures and pressures, of the binary systems versus compositions were semiempirically evaluated. It was found experimentally that there is an area of parameters in the PTx phase diagram, for each pair of vapor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…These measurements have been made using a static diffusion cloud chamber at pressures up to 4.0 MPa with H 2 , He, N 2 , and Ar as the carrier gases. Other experimental results have supported a dependence of the nucleation rate on the nature and total pressure of the carrier gas (Anisimov, Koropchak et al, 2000;Luijten, Peeters, & van-Dongen, 1999;Lihavainen & Viisanen, 2001). Gas-pressure effects were detected by van Remoortere, Heath, Wagner, and Strey (1996) although most of the measurements from this research group (i.e., Viisanen, Strey, & Reiss, 1993; did not observe carrier gas influences on nucleation rate.…”
Section: Fig 8 A-criterion Application For Publishedsupporting
confidence: 57%
“…These measurements have been made using a static diffusion cloud chamber at pressures up to 4.0 MPa with H 2 , He, N 2 , and Ar as the carrier gases. Other experimental results have supported a dependence of the nucleation rate on the nature and total pressure of the carrier gas (Anisimov, Koropchak et al, 2000;Luijten, Peeters, & van-Dongen, 1999;Lihavainen & Viisanen, 2001). Gas-pressure effects were detected by van Remoortere, Heath, Wagner, and Strey (1996) although most of the measurements from this research group (i.e., Viisanen, Strey, & Reiss, 1993; did not observe carrier gas influences on nucleation rate.…”
Section: Fig 8 A-criterion Application For Publishedsupporting
confidence: 57%
“…The experimental study [28] at sufficiently high temperatures of 398.2, 423.2, and 453.2 K at a pressure up to 55 MPa showed that this is type V-VI of phase behavior with a discontinuous critical curve. However, Anisimov et al [29], in their study concerning only nucleation in the supersaturated vapor of this system near the critical line, stated that this line is continuous. To be sure, this statement was not grounded in the results of experimental investigations of the phase space, but was formulated only based on some theoretical and calculated concepts.…”
Section: Resultsmentioning
confidence: 86%
“…By contrast, according to Eqn (25), this value is inverse to the cube of the logarithm of supersaturation. However, the linear regressions of the experimental nucleation rates both as the functions (lnS) 73 and (lnS) 72 give equally good approximations.…”
Section: Modifications Of the Classical Nucleation Theorymentioning
confidence: 99%